2021
DOI: 10.1021/acs.jchemed.1c00758
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Remote Chemistry Lecture Delivery Methods

Abstract: Beginning in March 2020, instructors and students in educational institutions across the world have had to adapt to new virtual methods of teaching and learning. This study focused on obtaining the student perspective of remote chemistry lecture delivery methods across 13 Fall 2020 courses with students in varied majors of study and stages of degree completion. For students who experienced a mixture of asynchronous and synchronous content delivery within the same course, a majority of students preferred the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Although our recommendations on the flipped classroom setup were originally tailored to the COVID-19 pandemic online environment, the strategies were successfully implemented in an in-person flipped active learning class during Spring 2022. As best practice, in agreement with Accettone, we recommend maintaining at least some of the flexibility of asynchronous learning in a well-organized study environment with clear expectations and guidelines. The flipped classroom model should not be used as a “default” best practice, rather as a tool to facilitate the learning of lower-level concepts at home and building up on those by evidence-based techniques to promote higher level learning in class.…”
Section: Limitations Implications and Concluding Remarksmentioning
confidence: 93%
See 1 more Smart Citation
“…Although our recommendations on the flipped classroom setup were originally tailored to the COVID-19 pandemic online environment, the strategies were successfully implemented in an in-person flipped active learning class during Spring 2022. As best practice, in agreement with Accettone, we recommend maintaining at least some of the flexibility of asynchronous learning in a well-organized study environment with clear expectations and guidelines. The flipped classroom model should not be used as a “default” best practice, rather as a tool to facilitate the learning of lower-level concepts at home and building up on those by evidence-based techniques to promote higher level learning in class.…”
Section: Limitations Implications and Concluding Remarksmentioning
confidence: 93%
“…58 For example, even email could be considered a near-synchronous method of communication, if users monitor their emails continuously. 59 Accettone 60 recently published a manuscript on student's perspective of remote chemistry lecture delivery methods across 13 Fall 2020 courses. It was found that students, when given the choice, preferred hybrid content delivery, indicating more flexibly of the asynchronous learning and interaction with the instructor and peers of synchronous learning as the reason for the choice, in alignment with our findings.…”
Section: Student Feedback -Surveymentioning
confidence: 99%
“…Previous studies found that students had favorable attitudes about asynchronous lectures, whereas students preferred pre-recorded courses uploaded to Google Classroom or YouTube. This feature allows students to listen to lecture recordings repeatedly to understand the material better (Accettone, 2021;Prabawangi et al, 2021).…”
Section: Synchronous and Asynchronous Lecturesmentioning
confidence: 99%
“…Regarding online education and distance learning, Accettone investigated students’ perceptions of lecture delivery models for remote chemistry lectures and laboratories. , While the students preferred the asynchronous model of instruction for lectures, they noted that in-person laboratory sessions provided better learning and practice opportunities . In synchronous online chemistry laboratories, Livestream tends to be more satisfying for students than prerecorded videos …”
Section: Introductionmentioning
confidence: 99%